2017
DOI: 10.1002/14651858.cd007984.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Family Group Decision Making for children at risk of abuse and neglect

Abstract: The editorial group responsible for this previously published document have withdrawn it from publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Three studies were reported in two study reports. Baumann (2006) and Sheets et al (2009), reported findings from the same study. Baumann reported findings on the nature of children's placements, Sheets et al reported some of these findings, but also additional findings related to service user satisfaction.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…Three studies were reported in two study reports. Baumann (2006) and Sheets et al (2009), reported findings from the same study. Baumann reported findings on the nature of children's placements, Sheets et al reported some of these findings, but also additional findings related to service user satisfaction.…”
Section: Resultsmentioning
confidence: 61%
“…Sheets et al (2009) compared survey responses from FGDM and non‐FGDM parents and relatives under three headings: satisfaction with family plan; understanding of what was expected of them; and sense of empowerment. Data were collected using an unvalidated 5‐point rating scale and sample sizes ranged from 50 to 636.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations